Characterization of Lifestyle in Spinocerebellar Ataxia Type 3 and Association with Disease Severity. Issue 2 (29th October 2021) - Hengel, Holger; Martus, Peter; Faber, Jennifer; Garcia‐Moreno, Hector; Solanky, Nita; Giunti, Paola; Klockgether, Thomas; Reetz, Kathrin; van de Warrenburg, Bart P.; Pereira de Almeida, Luís; Santana, Magda M.; Januário, Cristina; et al.
ABSTRACT: Background: Lifestyle could influence the course of hereditary ataxias, but representative data are missing. Objective: The objective of this study was to characterize lifestyle in spinocerebellar ataxia type 3 (SCA3) and investigate possible associations with disease parameters. Methods: In a prospective cohort study, data on smoking, alcohol consumption, physical activity, physiotherapy, and body mass index (BMI) were collected from 243 patients with SCA3 and 119 controls and tested for associations with age of onset, disease severity, and progression. Results: Compared with controls, patients with SCA3 were less active and consumed less alcohol. Less physical activity and alcohol abstinence were associated with more severe disease, but not with progression rates or age of onset. Smoking, BMI, or physiotherapy did not correlate with disease parameters. Conclusion: Differences in lifestyle factors of patients with SCA3 and controls as well as associations of lifestyle factors with disease severity are likely driven by the influence of symptoms on behavior. No association between lifestyle and disease progression was detected. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society